The Role of CHPD and AIMI processing on enhancing JC and transverse connectivity of in-situ MgB2 strand. Issue 1 (March 2020) - Wan, F; Sumption, M D; Rindfleisch, M A; Collings, E W
Abstract: Research into in-situ MgB2 strand has been focused on improvements in JC through reduction of porosity. Both of cold-high-pressure-densification (CHPD) and advanced-internal-magnesium-infiltration (AIMI) techniques can effectively remove the voids in in-situ MgB2 strands. This study shows the nature of the reduced porosity for in-situ MgB2 strands lies on increases in transverse grain connectivity as well as longitudinal connectivity. The CHPD method bi-axially applying 1.0 GPa and 1.5 GPa yielded 4.2 K J CM║ s of 9.6 × 10 4 A/cm 2 and 8.5 × 10 4 A/cm 2 at 5 T, respectively, with compared with 6.0 × 10 4 A/cm 2 for typical powder-in-tube (PIT) in-situ strand. Moreover, AIMI-processed monofilamentary MgB2 strand obtained even higher J C s and transverse grain connectivity than the CHPD strands.